2018
DOI: 10.1021/acsami.8b04733
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy to Low-Cost Synthesis of Hierarchically Porous, Active Carbon of High Graphitization for Energy Storage

Abstract: To achieve high energy/power output, long serving life, and low cost of carbon-based electrodes for energy storage, we have developed a unique synthesis method for the fabrication of hierarchically porous carbon of high graphitization (HPCHG), derived from pyrolysis of an iron-containing organometallic precursor in a molten ZnCl media at relatively low temperatures. The as-prepared HPCHG has a large specific surface area (>1200 m g), abundant micro/mesopores, and plenty of surface defects. When tested in a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…After carbonization, the carbon precursors are converted into graphitizable or nongraphitizable carbon. Direct graphitization of graphitizable carbon at high temperature (~3000°C) and catalytic graphitization of non-graphitizable carbon at a temperature of~1000°C are the two primary routes of transforming amorphous carbon into graphite 22,23 . Moreover, the transition metal catalysts are found to be difficult to separate from synthetic graphite 24 .…”
mentioning
confidence: 99%
“…After carbonization, the carbon precursors are converted into graphitizable or nongraphitizable carbon. Direct graphitization of graphitizable carbon at high temperature (~3000°C) and catalytic graphitization of non-graphitizable carbon at a temperature of~1000°C are the two primary routes of transforming amorphous carbon into graphite 22,23 . Moreover, the transition metal catalysts are found to be difficult to separate from synthetic graphite 24 .…”
mentioning
confidence: 99%
“…Till now, various strategies have been proposed to develop porous structure, including carbonization under KOH, 9 ZnCl 2 (ref. 10 and 11 ) and CO 2 . 12 Despite the remarkable increase in the SSA value and pore size after activation, most materials display unsatisfied specific capacitance because of the low conductivity.…”
Section: Introductionmentioning
confidence: 95%
“…It is found that Cu ions in Cu-BTC can react with carboxyl, hydroxyl, and sulfonic groups on carbon-based materials, which can reduce the influence of water to some extent and improve the selectivity of some gases (such as NH 3 ) [131,149]. Of course, some methods have been adopted in the experiment to improve the hydrophobicity further, mainly introducing hydrophobic groups or hydrophobic substances [150][151][152][153][154]. For example, Nasim et al used hydrophobic ZIF-8 to compound MWCNTs and silver nanoparticles.…”
Section: The Choice Of Carbon-based Materials and Mof Materialsmentioning
confidence: 99%